Microscopic series plug-in hybrid electric vehicle energy consumption model: Model development and validation. (August 2018) - Fiori, Chiara; Ahn, Kyoungho; Rakha, Hesham A.
Highlights: A novel microscopic energy model for plug-in hybrid electric vehicles is developed. Braking energy regeneration efficiency varies with deceleration level. The model can be adopted in traffic simulation models and smartphone applications. This model can be calibrated using publically available data. Abstract: Plug-in hybrid electric vehicles (PHEVs) significantly improve vehicle fuel efficiency compared to conventional internal combustion engine vehicles (ICEVs) and also eliminate the "range anxiety" associated with battery-only electric vehicles (BEVs). This paper develops a simple PHEV energy consumption model that can be used in a real-time in-vehicle and smartphone eco-driving application, an eco-routing navigation system, and/or a microscopic traffic simulation software. The majority of PHEV studies have centered on the evaluation of energy consumption to analyze vehicle control strategies or the behavior of the battery system assuming an average constant value for the regenerative braking energy efficiency or regenerative braking factors that are principally dependent on the vehicle's average speed. The proposed series PHEV energy consumption model estimates a PHEV's instantaneous energy consumption using second-by-second vehicle speed, acceleration, and roadway grade data as input variables accounting for the regenerative braking efficiency using instantaneous vehicle parameters. The model developed in this study computes the vehicle's energy consumption producing an average error of 4% relative to independently collected field data. Results show that PHEVs can recover a higher amount of energy in urban driving when compared to high speed highway driving. Finally, it is important to highlight the fact that this model is flexible and general and thus can model different PHEVs as there is no need for efficiency maps for the electric motor or the internal combustion engine.